PEREMPUAN DESA PETATAL DIDORONG KUASAI LITERASI DIGITAL DAN BERDAYA DI ERA GLOBALISASI - Susi Masniari Nasution; Diki Darmawan; Haris Munandar; Putri Amelia; Suci Suci (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: This study aims to analyze the role of digital literacy in empowering women in Petatal Village, Datuk Tanah Datar District, Batubara Regency. Digital literacy is a crucial need in the era of globalization, enabling women to adapt, become empowered, and contribute to village socio-economic development. The method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation of the Socialization of the Role of Digital Literacy in Developing Women's Economic Potential and Character in the Era of Globalization, implemented by the KKNT Team of the Faculty of Teacher Training and Education, Asahan University. The results showed that the socialization activity was able to increase women's knowledge, skills, and confidence in utilizing digital technology productively. Petatal Village women began to understand the importance of utilizing digital media for micro-enterprises, learning, and social communication. In addition, this activity fostered awareness of media ethics and a spirit of economic independence through local innovations such as making soap from used cooking oil. Thus, digital literacy has proven to be an effective means of increasing the independence, participation, and competitiveness of village women amidst the challenges of globalization.Keywords: Women's Empowerment, Digital Literacy, Petatal Village, Globalization, Economic IndependenceÂ Abstrak:Â Penelitian ini bertujuan untuk menganalisis peran literasi digital dalam pemberdayaan perempuan di Desa Petatal, Kecamatan Datuk Tanah Datar, Kabupaten Batubara. Literasi digital menjadi kebutuhan penting di era globalisasi agar perempuan mampu beradaptasi, berdaya, dan berkontribusi dalam pembangunan sosial ekonomi desa. Metode yang digunakan adalah deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi kegiatan Sosialisasi Peran Literasi Digital untuk Mengembangkan Potensi Perekonomian dan Karakter Perempuan di Era Globalisasi yang dilaksanakan oleh Tim KKNT FKIP Universitas Asahan. Hasil penelitian menunjukkan bahwa kegiatan sosialisasi mampu meningkatkan pengetahuan, keterampilan, dan kepercayaan diri perempuan dalam memanfaatkan teknologi digital secara produktif. Perempuan Desa Petatal mulai memahami pentingnya pemanfaatan media digital untuk usaha mikro, pembelajaran, dan komunikasi sosial. Selain itu, kegiatan ini menumbuhkan kesadaran akan etika bermedia serta semangat kemandirian ekonomi melalui inovasi lokal seperti pembuatan sabun dari minyak jelantah. Dengan demikian, literasi digital terbukti menjadi sarana efektif untuk meningkatkan kemandirian, partisipasi, dan daya saing perempuan desa di tengah tantangan globalisasi.Kata Kunci: Pemberdayaan Perempuan, Literasi Digital, Desa Petatal, Globalisasi, Kemandirian Ekonomi